PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR - Nur'ula Khairiyah, Siti Metha; Asri Pujiasti, Dea (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses the role of teachers in increasing student learning motivation. Learning motivation is the main driving factor for students to achieve their academic goals. In this article, the author defines what learning motivation is, explains the various forms of motivation, and examines how teachers act as motivators. Apart from that, this article presents various strategies that can be implemented by teachers to increase student motivation, such as implementing interesting learning methods, creating healthy competition, and providing awards or praise. In conclusion, the role of the teacher as a motivate or is very important in creating a positive learning environment and encouraging students to study harder in order to achieve maximum achievement